ON TEMPORARY SYNTACTIC AMBIGUITY - ALINA PREDA (Studia Universitatis Babes-Bolyai, 2010)
ABSTRACT. Syntactic ambiguity is a feature displayed by a complex expression which may have more than one meaning, due to the possibility of interpreting its grammatical structure (at one point or another in the sentence) in more than one way. An instance of syntactic ambiguity leads to a network of alternative attachments, and temporary ambiguity occurs when there may be more than one possible syntactic structure for one part of a sentence. Sentences marked by temporary ambiguity cause the human sentence processor to construct an initial syntactic structure which turns out to be incorrect and, consequently, they require, at a certain point, both syntactic and semantic reanalysis.